Cases on Innovation and Sustainability in Tourism - Dias, Á. (2024)
The tourism industry faces a critical challenge: balancing its economic benefits with the growing environmental and social impacts it generates. This delicate equilibrium calls for innovative solutions that drive sustainability while maintaining financial viability. Cases on Innovation and Sustainability in Tourism presents a compelling response to this challenge, offering insightful case studies showcasing successful innovations in sustainable tourism practices. By highlighting these innovative solutions, the book provides a roadmap for industry stakeholders to adopt sustainable practices without compromising profitability. Through a diverse range of cases, this book demonstrates how emerging technologies, innovative business models, and destination management strategies can contribute to a more sustainable tourism industry. Academics, practitioners, and policymakers will find valuable insights and inspiration within these pages, encouraging them to implement similar initiatives in their organizations and regions. This book is a must-read for anyone involved in the tourism industry, from academics and researchers to industry professionals and policymakers. It offers a comprehensive overview of the latest trends and innovations in sustainable tourism, providing practical guidance for those looking to make a positive impact.